Increased Risk of ADHD at Short and Long Interpregnancy Intervals in a National Birth Cohort - Cheslack‐Postava Keely; Sourander Andre; Suominen Auli; Jokiranta‐Olkoniemi Elina; McKeague Ian W.; Brown Alan S. (Wiley Online Library, 2022)
Background
Short or long interpregnancy interval (IPI) may adversely impact conditions for foetal development. Whether attention deficit hyperactivity disorder (ADHD) is related to IPI has been largely unexplored.
Objectives
To examine the association between IPI and ADHD in a large, population‐based Finnish study.
Methods
All children born in Finland between 1991 and 2005 and diagnosed with ADHD (ICD‐9 314x or ICD‐10 F90.x) from 1995 to 2011 were identified using data from linked national registers. Each subject with ADHD was matched to 4 controls based on sex, date of birth, and place of birth. A total of 9564 subjects with ADHD and 34,479 matched controls were included in analyses. IPI was calculated as the time interval between sibling birth dates minus the gestational age of the second sibling. The association between IPI and ADHD was determined using conditional logistic regression and adjusted for potential confounders.
Results
Relative to births with an IPI of 24 to 59 months, those with the shortest IPI (<6 months) had an increased risk of ADHD (odds ratio [OR] 1.30, 95% confidence interval (CI) 1.12, 1.51) and the ORs for the longer IPI births (60‐119 months and ≥120 months) were 1.12 (95% CI 1.02, 1.24) and 1.25 (95% CI 1.08, 1.45), respectively. The association of longer IPI with ADHD was attenuated by adjustment for maternal age at the preceding birth, and comorbid autism spectrum disorders did not explain the associations with ADHD.
Conclusions
The risk of ADHD is higher among children born following short or long IPIs although further studies are needed to explain this association.